Ag / TiO2 / GO doped PAN photocatalytic membrane as well as preparation method and application thereof
By combining the Ag/TiO2/GO composite material with the PAN film and using electrospinning technology to prepare the photocatalytic film, the existing PAN photocatalytic film has been solved, and the high-efficiency photocatalytic and anti-pollution performance has been improved.
Patent Information
- Application Number
- CN202411919392.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-25
AI Technical Summary
The existing PAN photocatalytic efficiency of the photocatalytic film is low, and photocatalytic materials are prone to photocorrosion under long-term light, resulting in a decrease in photocatalytic effect.
Ag/TiO2/GO composite material is used to combine with PAN film, and an Ag/TiO2/GO doped PAN photocatalytic film is prepared through electrospinning technology to improve photocatalytic performance and anti-pollution ability.
The photocatalytic activity and anti-pollution performance of the photocatalytic film are significantly improved, the service life of the film is extended, the absorption range of light is improved, and the utilization rate of light is enhanced.
Smart Images

Figure CN119733559A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of catalytic films, and in particular relates to an Ag / TiO2 / GO doped PAN photocatalytic film and a preparation method and application thereof. Background Art
[0002] As the contradiction between the growing energy demand and the increasing energy shortage intensifies, the development and utilization of new energy, especially solar energy, has become more important. Photocatalysis has attracted much attention from researchers due to its mild reaction conditions and its ability to directly convert solar energy into chemical energy.
[0003] Photocatalytic technology refers to the process in which a photocatalyst absorbs light energy under external light radiation, excites conduction band electrons and valence band holes, and adsorbs on the catalyst surface to undergo chemical reactions. The photocatalytic process of PAN film is divided into the following steps: PAN film is used as a matrix to load the photocatalytic material. When light reaches the TiO2-PAN film, the photocatalytic material absorbs light energy to produce excited electrons and holes. Under the action of light absorption, the excited electrons and holes react to produce active oxygen species, such as hydroxyl radicals (·OH), superoxide radicals (·O 2- ) and so on. These reactive oxygen species have strong oxidizing ability and can react with organic pollutants, bacteria, etc. Reactive oxygen species undergo oxidation reactions with organic pollutants, bacteria, etc. For example, hydroxyl radicals can decompose organic pollutants into smaller harmless substances through oxidation reactions. Superoxide radicals can react with structures such as bacterial cell walls, destroying their structures and achieving a bactericidal effect. After the photocatalytic reaction, the reaction products produced will be released into the environment. Depending on the reactants and reaction conditions, the reaction products can be harmless substances such as water and carbon dioxide.
[0004] PAN photocatalytic film is widely used, with advantages such as wide wavelength response, reusability, and strong controllability. However, the photocatalytic efficiency of PAN photocatalytic film is relatively low, and a long illumination time is required to achieve effective degradation or sterilization. This is mainly due to factors such as low activity of photocatalytic materials and low light absorption efficiency. The photocatalytic materials in PAN photocatalytic film are prone to photocorrosion and structural damage under long-term illumination, resulting in a decrease in photocatalytic effect. This limits the long-term stability and durability of the photocatalytic film.
[0005] In the prior art, PAN is combined with other semiconductor materials (such as TiO2, ZnO, CdS, etc.) to form a heterojunction, which can promote the effective separation of electron-hole pairs, reduce the recombination probability of carriers, and improve the photocatalytic performance. However, there are problems such as complex preparation process, high cost, and poor interface matching between different materials, which may lead to poor contact and affect the charge transfer efficiency.
[0006] Therefore, researching a method with high efficiency and good stability is of utmost importance. Summary of the invention
[0007] The purpose of the present invention is to provide a Ag / TiO2 / GO doped PAN photocatalytic film and its preparation method and application. The present invention prepares an Ag / TiO2 / GO composite material with excellent photocatalytic performance and adds it to the PAN film, which can greatly improve the film's light absorption capacity, catalytic performance and anti-pollution ability.
[0008] In order to achieve the above object, the present invention provides the following technical solutions:
[0009] A method for preparing a Ag / TiO2 / GO doped PAN photocatalytic film comprises the following steps:
[0010] (1) Mixing a mixed modified graphene oxide powder, tetrabutyl titanate, and silver nitrate in a mass ratio of 1: (1-5): 1, adding the mixture to a water / ethanol mixture, stirring evenly to obtain a mixed solution, adding the mixed solution to a sealed container, heating to 80-120° C. and maintaining the constant temperature for 1-3 hours; after the reaction is completed, cooling to room temperature, centrifugation washing, and freeze-drying to obtain an Ag / TiO2 / GO composite material; the mixed modified graphene oxide powder includes chitosan modified graphene oxide powder and amino modified graphene oxide powder in a mass ratio of (2-3): 1;
[0011] (2) adding Ag / TiO2 / GO composite material and PAN in a mass ratio of 1:(5-15) into N,N-dimethylformamide, stirring with magnetic force at 45-60°C for 30-120 min until completely dissolved, and then standing at a constant temperature of 32-35°C for degassing to obtain a spinning solution;
[0012] (3) Add the spinning solution into the syringe, fix the syringe on the micro-injection pump, connect the needle of the injection pump to the positive electrode of the high-voltage power supply, and connect the negative electrode to the receiving roller; control the electrospinning positive voltage to 15-18 kV, the negative voltage to -1.5 kV, the distance from the receiving roller to the needle to 5-15 cm, and the spinning solution flow rate to 0.5-1.5 mL / h for electrospinning to obtain Ag / TiO2 / GO doped PAN photocatalytic film.
[0013] Furthermore, the preparation method of the chitosan-modified graphene oxide powder comprises the following steps:
[0014] (1) dispersing 1 part by mass of graphene oxide powder A in 10-15 parts by mass of deionized water, ultrasonically dispersing for 1-3 hours, adding 0.04-0.07 parts by mass of silane coupling agent KH550, reflux reacting at 40-45° C. for 3-5 hours, and centrifuging to obtain silane-modified graphene oxide powder;
[0015] (2) dispersing the silane-modified graphene oxide powder prepared in step (1) in 10-15 parts by weight of methanol, ultrasonically dispersing for 1-3 hours, adding 0.06-0.08 parts by weight of glutaraldehyde in a water bath at 40-45° C., and adding 0.01-0.015 parts by weight of acetic acid dropwise, and reflux reacting for 3-5 hours; adding a dilute nitric acid solution of chitosan, and continuing to reflux reacting at 40-45° C. for 3-6 hours. After the reaction is completed, centrifugation is performed to obtain chitosan-modified graphene oxide powder.
[0016] Commercially available graphene oxide is prone to agglomeration, which affects the loading effect of titanium oxide and silver. The present invention can improve the photocatalytic degradation activity of the photocatalytic film by modifying graphene oxide with chitosan. Chitosan can form a protective film on the surface of GO to prevent GO sheets from agglomerating, maintaining its dispersibility and large specific surface area. This helps to expose more active sites to participate in the photocatalytic reaction. Chitosan molecules contain a large number of amino and hydroxyl groups. These functional groups can not only serve as adsorption sites to fix organic pollutants, but also interact with photogenerated holes or electrons to generate more reactive oxygen species (ROS), such as hydroxyl radicals (·OH) and superoxide anion radicals (·O2 - ). These active species can more effectively degrade organic pollutants and improve the efficiency of photocatalytic degradation. Chitosan, as a natural polymer, has good film-forming properties and mechanical strength. It can help PAN fibers form a denser and more uniform network structure, improving the overall stability and durability of the photocatalytic film. This means that the photocatalytic film is not easily damaged or inactivated during long-term use and can maintain a high catalytic activity. Chitosan-modified GO works together with Ag and TiO2 to form a multi-component synergistic system. Ag nanoparticles can act as electron traps to further promote charge separation; TiO2 provides efficient photocatalytic activity; and chitosan-modified GO enhances the stability and light absorption capacity of the material. This synergistic effect has comprehensively improved the performance of the entire photocatalytic film.
[0017] Furthermore, the mass ratio of the graphene oxide powder A to chitosan is 1:(0.2-0.3).
[0018] Furthermore, the concentration of the dilute nitric acid is 0.1-0.15 mol / L. The mass ratio of chitosan to the dilute nitric acid is 1:(3-5).
[0019] Furthermore, the size of the graphene oxide powder A is 1 to 3 μm; the number of layers: 1 to 3 layers.
[0020] Furthermore, the preparation method of the amino-modified graphene oxide powder comprises the following steps:
[0021] (1) adding graphene oxide powder B to deionized water, and ultrasonically dispersing at 0-5° C. for 30-40 min to obtain a graphene oxide dispersion, wherein the concentration of the graphene oxide is 0.1-0.2 g / L;
[0022] (2) Adding 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide to the graphene oxide dispersion, stirring with magnetic force in an ice bath, and obtaining a mixed solution; continuing to add ethylenediamine, reacting for 13-15 hours, and washing the product thoroughly with acetone / deionized water, and drying to obtain amino-modified graphene oxide powder.
[0023] In order to improve the water-oil separation performance of the photocatalytic membrane, the present invention adds amino-modified graphene oxide to the system, and compounding it with chitosan-modified graphene oxide powder in a specific ratio, the two play a synergistic role, and the water-oil separation performance of the photocatalytic membrane can be improved, especially for water-in-hexane emulsions, it has an excellent separation effect. By compounding chitosan-modified graphene oxide (CS-GO) and amino-modified graphene oxide (NH2-GO) in a specific ratio, the hydrophilic effect in the photocatalytic membrane can be improved, and its water-oil separation performance can be significantly improved, especially for water-in-hexane emulsions, it has an excellent separation effect.
[0024] Furthermore, the amount of ethylenediamine added is 2-7% of the volume of the mixed solution.
[0025] Furthermore, the added amount of the 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide is 20-30% of the mass of the graphene oxide.
[0026] Furthermore, the added amount of the N-hydroxysuccinimide is 20-30% of the mass of the graphene oxide.
[0027] Furthermore, the size of the graphene oxide powder B is 1 to 3 μm; the number of layers: 1 to 3 layers.
[0028] Furthermore, the ratio of the total mass of the mixed modified graphene oxide powder, tetrabutyl titanate, and silver nitrate to the mass of the mixed solution of water and ethanol is 1:(7-10).
[0029] Furthermore, the mass ratio of water to ethanol in the water / ethanol mixture is 1:(1-5).
[0030] Furthermore, the total mass of the Ag / TiO2 / GO composite material and PAN:N,N-dimethylformamide mass ratio is 1:(8-12).
[0031] The invention provides an Ag / TiO2 / GO doped PAN photocatalytic film prepared by the preparation method.
[0032] The third aspect of the present invention provides the application of the Ag / TiO2 / GO doped PAN photocatalytic film, and the application of the Ag / TiO2 / GO doped PAN photocatalytic film in air purification, sewage treatment, and antibacterial clothing.
[0033] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0034] 1. In order to solve the problems of relatively low photocatalytic efficiency of TiO2-PAN photocatalytic film, and TiO2 is prone to photocorrosion and structural damage under long-term illumination, the present invention prepares Ag / TiO2 / GO, a catalytic material with excellent catalytic performance and excellent compatibility, through a "one-step method", and then adds Ag / TiO2 / GO to PAN to prepare Ag / TiO2 / GO-PAN photocatalytic film by electrospinning. The present invention uses an electrospinning method to spin PAN spinning solution containing the required components, with simple steps and practical methods.
[0035] 2. The present invention utilizes the characteristics of GO nanosheets, such as large specific surface area, high electron mobility, and many active sites, and loads TiO2 and Ag onto GO through a simple solution method to obtain a catalyst with excellent performance. Among them, TiO2 has high chemical stability, is non-toxic, and has excellent photocatalytic performance. Ag can effectively capture the photogenerated electrons generated in the system, and has the unique surface plasmon resonance effect of precious metals. Subsequently, Ag / TiO2 / GO is loaded on PAN to obtain Ag / TiO2 / GO-PAN photocatalytic film, which can not only greatly improve the photocatalytic activity of the photocatalytic film, but also expand the light absorption range of the photocatalytic film to the visible light region, significantly enhancing the utilization rate of light.
[0036] 3. The method for preparing PAN photocatalytic film by electrospinning of the present invention is simple to operate and low in cost. A new type of high-efficiency photocatalyst Ag / TiO2 / GO is prepared by loading TiO2 and Ag onto GO. The catalyst has good compatibility with PAN and can effectively solve the problem of uneven distribution of TiO2 catalyst in the PAN matrix. In addition, the catalyst can enhance the light absorption capacity of the PAN film, promote the separation of electrons and holes, accelerate electron transmission, and improve anti-pollution performance, thereby improving the stability of the photocatalytic performance of the PAN film.
[0037] 4. The present invention can improve the photocatalytic degradation activity and stability of the photocatalytic film by modifying graphene oxide with chitosan.
[0038] 5. The present invention adds amino-modified graphene oxide to the system and compounding it with chitosan-modified graphene oxide powder in a specific ratio. The two play a synergistic role and can improve the water-oil separation performance of the photocatalytic membrane, especially having an excellent separation effect on water-in-hexane emulsion. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 Schematic diagram of the preparation process of Ag / TiO2 / GO-PAN photocatalytic film.
[0040] Figure 2 SEM images of TiO2-PAN film (a) and Ag / TiO2 / GO-PAN film (b).
[0041] Figure 3 Schematic diagram of the methyl orange decolorization rate of TiO2-PAN film and Ag / TiO2 / GO-PAN film. DETAILED DESCRIPTION
[0042] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0043] The raw materials used in the present invention are all commercially available products:
[0044] PAN: Polyacrylonitrile powder, Hubei Kemaidi Chemical Co., Ltd., molecular weight 90,000.
[0045] 1-Ethyl-3-(3-dimethylaminopropyl)carbodiimide (EDC), CAS No.: 25952-53-8.
[0046] N-Hydroxysuccinimide (NHS), CAS number: 5576-84-8.
[0047] Example 1
[0048] like Figure 1 As shown, this embodiment provides a Ag / TiO2 / GO doped PAN photocatalytic film, and its preparation method comprises the following steps:
[0049] (1) Mixing modified graphene oxide powder, tetrabutyl titanate, and silver nitrate in a mass ratio of 1:2:1, adding the mixture to a water / ethanol mixture, stirring evenly, obtaining a mixed solution, adding the mixed solution to a sealed container, heating to 100°C for 2 hours; after the reaction is completed, cooling to room temperature, centrifugation washing, and freeze drying to obtain an Ag / TiO2 / GO composite material; the mixed modified graphene oxide powder includes chitosan modified graphene oxide powder and amino modified graphene oxide powder in a mass ratio of 2.4:1; the total mass of the mixed modified graphene oxide powder, tetrabutyl titanate, and silver nitrate: the mass of the water and ethanol mixture is 1:8. The mass ratio of water to ethanol in the water / ethanol mixture is 1:3.
[0050] (2) Adding Ag / TiO2 / GO composite material and PAN in a mass ratio of 1:10 into N,N-dimethylformamide, magnetically stirring at 50°C for 60 min until completely dissolved, and then standing at a constant temperature of 35°C for degassing to obtain a spinning solution; the total mass of the Ag / TiO2 / GO composite material and PAN:N,N-dimethylformamide mass ratio is 1:10.
[0051] (3) Add the spinning solution into the syringe, fix the syringe on the micro-injection pump, connect the needle of the injection pump to the positive electrode of the high-voltage power supply, and connect the negative electrode to the receiving roller; control the electrospinning positive voltage to 16 kV, the negative voltage to -1.5 kV, the distance from the receiving roller to the needle to 10 cm, and the spinning solution flow rate to 1 mL / h for electrospinning to obtain Ag / TiO2 / GO doped PAN photocatalytic film.
[0052] The preparation method of the chitosan-modified graphene oxide powder comprises the following steps:
[0053] (1) Dispersing 1 part by mass of graphene oxide powder A in 12 parts by mass of deionized water, ultrasonically dispersing for 2 hours, adding 0.05 parts by mass of silane coupling agent KH550, reflux reacting at 42° C. for 4 hours, and centrifuging to obtain silane-modified graphene oxide powder; the size of graphene oxide powder A is 1 to 3 μm; the number of layers: 1 to 3 layers.
[0054] (2) The silane-modified graphene oxide powder prepared in step (1) is dispersed in 12 parts by mass of methanol, ultrasonically dispersed for 2 hours, and 0.07 parts by mass of glutaraldehyde is added in a water bath at 42°C, and 0.012 parts by mass of acetic acid is added dropwise, and refluxed for 4 hours; a dilute nitric acid solution of chitosan is added, and the concentration of the dilute nitric acid is 0.12 mol / L. The mass ratio of chitosan to dilute nitric acid is 1:4. The mass ratio of the graphene oxide powder A to chitosan is 1:0.25; the reflux reaction is continued at 42°C for 5 hours. After the reaction is completed, centrifugation is performed to obtain chitosan-modified graphene oxide powder.
[0055] The preparation method of the amino-modified graphene oxide powder comprises the following steps:
[0056] (1) Adding graphene oxide powder B to deionized water, and ultrasonically dispersing at 5° C. for 35 min to obtain a graphene oxide dispersion, wherein the concentration of the graphene oxide is 0.15 g / L; the size of the graphene oxide powder B is 1 to 3 μm; and the number of layers is 1 to 3 layers.
[0057] (2) Add 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide to the graphene oxide dispersion, stir magnetically in an ice bath to obtain a mixed solution; continue to add ethylenediamine, wherein the amount of ethylenediamine added is 5% of the volume of the mixed solution; react for 14 hours, and the product is thoroughly washed with acetone / deionized water and dried to obtain amino-modified graphene oxide powder.
[0058] The amount of 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide added is 25% of the mass of graphene oxide. The amount of N-hydroxysuccinimide added is 25% of the mass of graphene oxide.
[0059] Comparative Example 1
[0060] This comparative example provides a photocatalytic film, and the preparation method comprises the following steps:
[0061] (1) Weigh 1 part by mass of TiO2 (particle size of 100-200 nm) and 10 parts by mass of PAN respectively, then add the two powders into 100 parts by mass of DMF, stir magnetically at 60°C for 80 min until completely dissolved, and then stand at 35°C for degassing to obtain a spinning solution.
[0062] (2) Add the spinning solution into the syringe, fix the syringe on the micro-injection pump, connect the needle of the injection pump to the positive electrode of the high-voltage power supply, and connect the negative electrode to the receiving roller; control the electrospinning positive voltage to 16 kV, the negative voltage to -1.5 kV, the distance from the receiving roller to the needle to 10 cm, and the spinning solution flow rate to 1 mL / h for electrospinning to obtain Ag / TiO2 / GO doped PAN photocatalytic film.
[0063] Comparative Example 2
[0064] The difference between this comparative example and Example 1 is that the mixed modified graphene oxide powder is replaced by graphene oxide powder, and the size of the graphene oxide powder is 1 to 3 μm; the number of layers is 1 to 3 layers.
[0065] Comparative Example 3
[0066] The difference between this comparative example and Example 1 is that the mixed modified graphene oxide powder is replaced by chitosan modified graphene oxide powder, and the preparation method of chitosan modified graphene oxide powder is the same as that of Example 1.
[0067] Comparative Example 4
[0068] The difference between this comparative example and Example 1 is that the mixed modified graphene oxide powder is replaced by amino-modified graphene oxide powder; and the preparation method of amino-modified graphene oxide powder is the same as that of Example 1.
[0069] Comparative Example 5
[0070] The difference between this comparative example and Example 1 is that the mixed modified graphene oxide powder includes chitosan-modified graphene oxide powder and amino-modified graphene oxide powder in a mass ratio of 1:2.5;
[0071] Performance Testing
[0072] (1) SEM test: A piece of the photocatalytic film prepared in Example 1 and Comparative Example 1 was cut to make a sample, and its morphology was observed under a scanning electron microscope.
[0073] Through SEM scanning electron microscope test ( Figure 2 ), it was found that the surface of the photocatalytic film of comparative example 1 was relatively smooth, and the surface of the photocatalytic film of embodiment 1 had more protrusions than the original film, indicating that the component substances of Ag / TiO2 / GO were indeed introduced into the photocatalytic film of embodiment 1.
[0074] (2) Photocatalytic test: 100 mg / L methyl orange 10 mL was added to 90 mL of distilled water to prepare a 10 mg / L methyl orange solution, and stirred to mix evenly. Then, the photocatalytic film prepared in Example 1 and Comparative Example 1 was fixed with iron wire and immersed in the solution. The solution was stirred for 1 hour in the dark, and a certain amount of the solution was taken every 1 hour for absorbance test. Then, 5 mg of PMS was weighed and added to the solution. The solution was stirred under xenon lamp irradiation, and a certain amount of the solution was taken every 10 minutes for absorbance test and recorded. The degradation rate η was calculated according to the formula η=(C0-C t / C0)×100%=(A0-A t / A0)×100%. , C0 is the concentration before degradation; Ct is the concentration after degradation.
[0075] In order to test the recycling performance of the sample, five cycle experiments were carried out, and the cyclic stability of the catalyst was characterized by comparing the photocatalytic degradation curves. Since the material is easy to recycle, after each cycle, the material was directly taken out of the solution, washed with distilled water and ethanol three times respectively, and then dried in an oven for the next use.
[0076] pass Figure 3 It can be seen that the photocatalytic performance of Example 1 has been significantly improved. The photocatalytic performance of the film is greatly improved due to the loading of GO material.
[0077] (3) Quantitative analysis of the photocatalytic degradation performance of tetracycline hydrochloride using an ultraviolet-visible spectrophotometer: A 300W Xe lamp was used as the irradiation light source. 50 mg of the photocatalytic film prepared in Example 1 and Comparative Examples 1-5 were placed in 50 mL of an aqueous solution of tetracycline hydrochloride, respectively, and the solution was stirred in a dark environment for 1 hour to achieve the adsorption-desorption equilibrium of the catalyst, during which a sample was taken every 30 minutes; the solution was irradiated with visible light (300W Xe lamp), and samples were taken every 20 minutes, and analyzed using an ultraviolet-visible spectrophotometer (ULTRA plus). The degradation rate of tetracycline hydrochloride within 240 minutes. Degradation rate = (C0-Ct / C0) × 100%, C0 is the concentration before degradation; Ct is the concentration after degradation.
[0078] (4) Stability: The photocatalytic films prepared in Example 1 and Comparative Examples 1-5 were subjected to 20 degradation cycle tests, and the degradation rate of tetracycline hydrochloride in the 20th cycle within 240 min was calculated.
[0079] (5) Oil-water separation: The organic carbon content of the solution before and after separation was analyzed using a total organic carbon analyzer. The n-hexane-in-water emulsion was tested separately. 20 mL of the oil-in-water emulsion was passed through a circular photocatalytic membrane with a diameter of 2 cm prepared in Example 1 and Comparative Examples 1-5. The organic carbon content in the solution before and after filtration was measured. The oil-water separation efficiency was calculated as (organic carbon content in the solution before filtration - after filtration) / organic carbon content in the solution before filtration × 100%.
[0080] The results are shown in Table 1.
[0081] Table 1 Performance test results
[0082]
[0083] From the above performance test results, it can be seen that Example 1 has good photodegradation effect, high stability, and good water-oil separation effect, and is a product with excellent comprehensive performance.
[0084] However, the comparative examples did not adopt the necessary technical solutions, resulting in that they were significantly worse than the embodiments in the corresponding performance tests. The photocatalytic performance of the material prepared by the preparation method in comparative example 1 was poor, no modification scheme was performed on graphene oxide in comparative example 2, and the compositions and proportions of the mixed modified graphite oxides in comparative examples 3-5 were different. The photodegradation effect of the photocatalytic film decreased, and the water-oil separation effect became worse. The above experimental results further prove the importance of the technical solutions defined in the present invention for its technical effects.
[0085] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing Ag / TiO2 / GO doped PAN photocatalytic film, characterized in that: The following steps are involved: (1) Mixing modified graphene oxide powder, tetrabutyl titanate, and silver nitrate in a mass ratio of 1:(1-5):1, adding the mixture to a water / ethanol mixture, stirring evenly to obtain a mixed solution, adding the mixed solution to a sealed container, heating to 80-120° C. for 1-3 hours; after the reaction is completed, cooling to room temperature, centrifugation washing, and freeze drying to obtain an Ag / TiO2 / GO composite material; The mixed modified graphene oxide powder comprises chitosan modified graphene oxide powder and amino modified graphene oxide powder in a mass ratio of (2-3):1; (2) adding Ag / TiO2 / GO composite material and PAN in a mass ratio of 1:(5-15) into N,N-dimethylformamide, stirring with magnetic force at 45-60°C for 30-120 min until completely dissolved, and then standing at a constant temperature of 32-35°C for degassing to obtain a spinning solution; (3) Add the spinning solution into the syringe, fix the syringe on the micro-injection pump, connect the needle of the injection pump to the positive electrode of the high-voltage power supply, and connect the negative electrode to the receiving roller; control the electrospinning positive voltage to 15-18 kV, the negative voltage to -1.5 kV, the distance from the receiving roller to the needle to 5-15 cm, and the spinning solution flow rate to 0.5-1.5 mL / h for electrospinning to obtain Ag / TiO2 / GO doped PAN photocatalytic film.
2. The method for preparing the Ag / TiO2 / GO doped PAN photocatalytic film according to claim 1, characterized in that: The preparation method of the chitosan-modified graphene oxide powder comprises the following steps: (1) dispersing 1 part by mass of graphene oxide powder A in 10-15 parts by mass of deionized water, ultrasonically dispersing for 1-3 hours, adding 0.04-0.07 parts by mass of silane coupling agent KH550, reflux reacting at 40-45° C. for 3-5 hours, and centrifuging to obtain silane-modified graphene oxide powder; (2) dispersing the silane-modified graphene oxide powder prepared in step (1) in 10-15 parts by weight of methanol, ultrasonically dispersing for 1-3 hours, adding 0.06-0.08 parts by weight of glutaraldehyde in a water bath at 40-45° C., and adding 0.01-0.015 parts by weight of acetic acid dropwise, and reflux reacting for 3-5 hours; adding a dilute nitric acid solution of chitosan, and continuing to reflux reacting at 40-45° C. for 3-6 hours. After the reaction is completed, centrifugation is performed to obtain chitosan-modified graphene oxide powder.
3. The method for preparing the Ag / TiO2 / GO doped PAN photocatalytic film according to claim 2, characterized in that: The mass ratio of the graphene oxide powder A to chitosan is 1:(0.2-0.3).
4. The method for preparing the Ag / TiO2 / GO doped PAN photocatalytic film according to claim 2, characterized in that: The size of graphene oxide powder A is 1 to 3 μm; the number of layers is 1 to 3 layers.
5. The method for preparing the Ag / TiO2 / GO doped PAN photocatalytic film according to claim 1, characterized in that: The preparation method of the amino-modified graphene oxide powder comprises the following steps: (1) adding graphene oxide powder B to deionized water, and ultrasonically dispersing at 0-5° C. for 30-40 min to obtain a graphene oxide dispersion, wherein the concentration of the graphene oxide is 0.1-0.2 g / L; (2) Adding 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide and N-hydroxysuccinimide to the graphene oxide dispersion, stirring with magnetic force in an ice bath, and obtaining a mixed solution; continuing to add ethylenediamine, reacting for 13-15 hours, washing, and drying to obtain amino-modified graphene oxide powder.
6. The method for preparing the Ag / TiO2 / GO doped PAN photocatalytic film according to claim 5, characterized in that: The size of graphene oxide powder B is 1 to 3 μm; the number of layers is 1 to 3 layers.
7. The method for preparing the Ag / TiO2 / GO doped PAN photocatalytic film according to claim 1, characterized in that: The ratio of the total mass of the mixed modified graphene oxide powder, tetrabutyl titanate, and silver nitrate to the mass of the mixed solution of water and ethanol is 1:(7-10).
8. The method for preparing the Ag / TiO2 / GO doped PAN photocatalytic film according to claim 1, characterized in that: The total mass of Ag / TiO2 / GO composite material and PAN:N,N-dimethylformamide mass ratio is 1:(8-12).
9. An Ag / TiO2 / GO doped PAN photocatalytic film prepared by the preparation method according to any one of claims 1 to 8.
10. An application of the Ag / TiO2 / GO doped PAN photocatalytic film prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The Ag / TiO2 / GO doped PAN photocatalytic film is used in air purification, sewage treatment, and antibacterial clothing.
Citation Information
Patent Citations
Preparation method of Ag-rGO-TiO2 nano-ring / nano-tube composite material
CN109908894A
Modified graphene oxide as well as preparation method and application thereof
CN110937598A
Preparation method of amphiphilic graphene oxide and surfactant containing amphiphilic graphene oxide
CN112777590A
Antibacterial ultraviolet-proof high-efficiency low-resistance micro-nanofiber mask fabric and preparation method thereof
CN115302866A
Method for preparing Ag-TiO2-rGO-PAN composite membrane with photocatalytic activity and sterilization performance
CN115787193A